2019
DOI: 10.1007/s10853-019-04014-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the initial microstructure and the loading conditions on the deformation behavior of the Ti17 titanium alloy

Abstract: In this work, the impact of the microstructure and the loading conditions on the mechanical behavior of a brich Ti17 titanium alloy is investigated. For this purpose, two different initial microstructures are considered : (i) a two-phase lamellar a ? b microstructure and (ii) a single-phase equiaxed b-treated microstructure. First, compression tests are performed at different strain rates (from 10 À1 to 10 s-1) and different temperatures (from 25 to 900 C) for both microstructures. Then, optical microscopy, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…At the strain rate of 1000 s −1 , multiple deformation mechanisms were comprehensively investigated in Ti-25Nb-3Zr-3Mo-2Sn, presenting the dynamic deformation sequences as {332}<113> and {112}<111> mechanical twining + stress-induced α” and ω phase transformations + dislocation slip at 293K → {332}<113> and {112}<111> mechanical twining + dislocation slip at 573K → dislocation slip only at 873 K [ 29 ]. The softening behavior of dual-phase Ti17 alloy (Ti-5Al-4Cr-4Mo-2Sn-2Zr) at a high temperature is attributed to the combinations of dynamic recrystallization, dynamic transformation, adiabatic heating, and morphological texture evolution [ 30 ]. Instead of thermal softening mechanisms, the microstructure evolutions or transformations play an important role in the initiation of ASB [ 21 , 24 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the strain rate of 1000 s −1 , multiple deformation mechanisms were comprehensively investigated in Ti-25Nb-3Zr-3Mo-2Sn, presenting the dynamic deformation sequences as {332}<113> and {112}<111> mechanical twining + stress-induced α” and ω phase transformations + dislocation slip at 293K → {332}<113> and {112}<111> mechanical twining + dislocation slip at 573K → dislocation slip only at 873 K [ 29 ]. The softening behavior of dual-phase Ti17 alloy (Ti-5Al-4Cr-4Mo-2Sn-2Zr) at a high temperature is attributed to the combinations of dynamic recrystallization, dynamic transformation, adiabatic heating, and morphological texture evolution [ 30 ]. Instead of thermal softening mechanisms, the microstructure evolutions or transformations play an important role in the initiation of ASB [ 21 , 24 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental procedure used for such tests is briefly described here. A detailed description of the experimental setup can be found in Ben-Boubaker et al (2020).…”
Section: Summary Of Experimental Resultsmentioning
confidence: 99%
“…For low temperatures (𝑇 ≤ 450 • C), the maximum error between the experimental and numerical curves does not exceed 6%. For temperatures above 700 • C, a yield drop phenomenon, which is attributed to either dynamic recrystallization Ben-Boubaker et al (2020) or the multiplication of mobile dislocations Teixeira et al (2007), is observed. This phenomenon is partly captured by the proposed model.…”
Section: Viscoplastic and Hardening Parameters Of The 𝛽 Phasementioning
confidence: 99%
“…In order to develop the advanced Ti alloys integrated the damage tolerance and high strength properties, a great amount of efforts have been completed investigating the high-strain rate shear behaviours of α Ti (Shahan and Taheri, 1993;Meyers et al, 1994;Chichili et al, 1998;Yang and Wang, 2006;Wang et al, 2007;Yang et al, 2010;Jiang et al, 2015;Kuang et al, 2017), Ti-6Al-4V alloy (Me-Bar andShechtman, 1983;Grebe et al, 1985;Da Silva and Ramesh, 1997;Lee and Lin, 1998;Timothy and Hutchings, 2013;Sun et al, 2014a;b;Mendoza et al, 2015;Zhou et al, 2017), TC16 (Wang, 2008), near-β Ti5551 (Ran and Chen, 2018) and Ti5553 (Yan and Jin, 2020), β ones (Zhan et al, 2016), α + β dual-phase ones (Yang et al, 2011b;Mantri et al, 2018;Ben Boubaker et al, 2019;Danard et al, 2019;Kloenne et al, 2020;Lee et al, 2020), and so on. It is worth mentioning that the dual-phase materials (Wu et al, 2017;Hao et al, 2021;Zou et al, 2021) always present ultra-strong and ductile behaviors combining the solid solution strengthening, grain refinement effect, and precipitation hardening, which could excellently deal with the planar-defects-dominated plastic deformation behaviors (Hao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional wellaccepted thermal-softening mechanism of ASB should be double checked, calling for more research efforts to reveal the microstructure evolutions resulting in the local softening (Guo et al, 2019). Therefore, it is necessary to reveal their corresponding softening mechanisms, including the dynamic recrystallization, dynamic transformation, adiabatic heating, and morphologies texture evolution (Yang and Wang, 2006;Rittel et al, 2008;Osovski et al, 2012;Li et al, 2017;Lieou and Bronkhorst, 2018;Ben Boubaker et al, 2019;Hao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%